Meningkatkan AktivitasvDan Hasil Belajar Keterampilan Berbicara Dengan Model Pembelajaran ProblemvBased Learning Kombinasi Metode Pembelajaran Bermain Peran - Sovia Hanisa; Mahmuddin (CV. ITTC INDONESIA, 2024)
The problem in this a research is a many students' have a low speaking skills and learning activities and a learning outcomes that do not reach the KKM. This is because learning is less interesting and one-way, the use of a learning model that is monotonous, students don't participate enough, low literacy and lack of attitude. speak well. The aims of this research is to find out how students' activities, learning outcomes and speaking skills are when using the Problem Based Learning learning model, a combination of Role Playing learning methods. The subjects of this research consisted of 11 students, namely 5 male students and 6 female students in class 5 of SDN Benua Anyar 9, North Banjarmasin subdistrict, in the second semester of the 2023/2024 academic year This research uses qualitative and quantitative approaches. The results of this research show that teacher activity at meeting I received a score of 25 in the